2015
DOI: 10.2147/ijn.s82818
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hexokinase-2 with targeted liposomal 3-bromopyruvate in an ovarian tumor spheroid model of aerobic glycolysis

Abstract: Background The objective of this study was to evaluate the expression levels of glycolytic markers, especially hexokinase-2 (HK2), using a three-dimensional multicellular spheroid model of human ovarian adenocarcinoma (SKOV-3) cells and to develop an epidermal growth factor receptor-targeted liposomal formulation for improving inhibition of HK2 and the cytotoxicity of 3-bromopyruvate (3-BPA). Methods Multicellular SKOV-3 tumor spheroids were developed using the hanging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…HK2 is regulated by the transcription factors such as p53, Myc, and HIF-1 [ 168 ]. Besides, the effective anticancer drug 3-bromopyruvate (3BP) is a structural analog of pyruvic acid, which plays the inhibitory effects on HK2 [ 169 171 ]. HK2 is characterized as an oncoprotein since its role in tumor onset [ 164 ].…”
Section: Hk2mentioning
confidence: 99%
“…HK2 is regulated by the transcription factors such as p53, Myc, and HIF-1 [ 168 ]. Besides, the effective anticancer drug 3-bromopyruvate (3BP) is a structural analog of pyruvic acid, which plays the inhibitory effects on HK2 [ 169 171 ]. HK2 is characterized as an oncoprotein since its role in tumor onset [ 164 ].…”
Section: Hk2mentioning
confidence: 99%
“…Some commonly used inhibitors include glucose analogs 2-deoxy-D-glucose (2-DG) and 3-bromopyruvate (3-BPA), which have been shown to induce cytotoxic effects on acute lymphoblastic leukemia while enhancing the efficacy of prednisone treatment [73,74]. An epidermal growth factor receptor-targeted liposomal formulation of 3-BPA showed improved permeability, HKII inhibition, and cytotoxicity compared with conventional aqueous 3-BPA formulations [75]. However, a recent study indicated that 3-BPA was still effective in killing HKII knockout cells, thus suggesting that in addition to HKII, the efficacy of 3-BPA may be also dependent on tumour microenvironment and glucose availability [76].…”
Section: Strategies To Target Mitochondriamentioning
confidence: 99%
“…Nevertheless, the acidic environment of the tumor milieu proves thermodynamically favorable for the uptake of 3-BP by cancer cells because of the pH difference across the plasma membrane (Azevedo-Silva et al, 2015). Another important reason for its selectivity against neoplastic cells is caused by the unmatched ability of 3-BP to alkylate and inactivate metabolic enzymes, which are selectively upregulated in malignant cells (Chen et al, 2009; Ganapathy-Kanniappan et al, 2009; Gandham et al, 2015; Azevedo-Silva et al, 2016; Jardim-Messeder and Moreira-Pacheco, 2016). Being an electrophile, 3-BP covalently and irreversibly modifies its targets’ nucleophilic moieties via S N 2 mechanism of alkylation (Azevedo-Silva et al, 2016; Oronsky et al, 2012) ( Figure 3 ).…”
Section: -Bromopyruvate Is Capable Of Multifaceted Targeting Of Tumomentioning
confidence: 99%
“…The main recommendations for overcoming the limitations regarding the use of 3-BP include strict implementation of only formulated preparations in human applications (El Sayed, 2018; Fan et al, 2019b), use of GSH scavengers accompanying 3-BP administration because GSH can inactivate 3-BP (El Sayed, 2018), and strict monitoring of the dose regimens (El Sayed, 2018). Furthermore, approaches of liposome-encapsulated 3-BP formulations are suggested to improve its adequate concentrations in the tumor milieu (Gandham et al, 2015). Use of 3-BP as an adjunct agent along with other conventional approaches is considered to hold therapeutic potential (Ganapathy-Kanniappan et al, 2013; Zhang et al, 2015; Chong et al, 2017).…”
Section: Limitations and Prospectsmentioning
confidence: 99%